The “Anjir” utterances in everyday communication of Gen-Z students - Zul Fauzi, Arief; Hasan, Imam; Kamal, Bahri; Setiawan, Fiki (CV. Eureka Murakabi Abadi, 2025)
This study aims to analyze the meaning and function of the word